ОСОБЛИВОСТІ СЛОВОТВІРНОЇ НОМІНАЦІЇ В ТЕРМІНОЛОГІЇ ВИБОРЧОГО ПРОЦЕСУ Й ВИБОРЧИХ ПРОЦЕДУР АНГЛІЙСЬКОЇ ТА УКРАЇНСЬКОЇ МОВ - Старченко, Олена Анатоліївна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2015)
Тhе article deals with the analysis of the main features of the word-building nomination in the terminology of the electoral process and electoral procedures in the English and Ukrainian languages. In the terminology in question the word-building nomination is connected with the formation of terminological units according to the linear and nonlinear models of derivatives. The first ones are formed Ьу adding some word-building elements (prefixal, suffixal and postfixational derivatives, compound words, abbreviations and shortenings). Тhе second is а result of transposing terms of one part of speech into another.